BASIC PRINCIPLES OF EXPERIMENTAL SIMULATION OF LIPOSUCTION AND ABDOMINOPLASTY - Trombola, O.V.; Atamanyuk, O.Yu. (World of Medicine and Biology, 2024)
According to forecasts, by 2035, 50 % of the world’s population will suffer from obesity, and we aimed to develop effective experimental models for the correction of its consequences, in the form of aesthetic defects of the anterior abdominal wall. By following a diet high in carbohydrates and saturated fat, obesity was achieved in 100 % of experimental animals. To ensure the possibility of conditional extrapolation of the obtained results to people, interventions and their combination were carried out in compliance with the basic principles of clinical operative technique. The rate of postoperative complications ranged from 7.1 % to 14.3 %, and changes in anthropometric parameters affected by obesity achieved aesthetic improvement and were characterized by statistical significance (p